Systematic Literature Review: The Implementation of Gamification in Mathematics Learning at Primary Schools - Tonioka, Nadya Hesty; Sutopo, Yeri; Ellianawati, Ellianawati; Kurniawan, Yunda; Avrilianda, Decky (Journal of Innovation and Research in Primary Education, 2025)
Mathematics education at the primary level faces significant challenges in maintaining student engagement and motivation, particularly with traditional teacher-centered approaches. Gamification, defined as the application of game elements to non-game educational contexts, has emerged as a promising solution to enhance mathematics learning outcomes. However, systematic examination of gamification research trends and effectiveness in primary mathematics education remains limited. This systematic literature review analyzed 15 peer-reviewed articles published between 2020 and 2025 focusing on gamification implementation in primary school mathematics education. Articles were systematically searched using Google Scholar with keywords "Gamification" and "Mathematics Learning." Inclusion criteria required studies to focus on primary education mathematics with quantitative, qualitative, or research and development methodologies. Data were extracted and analyzed to identify trends in research methods, publication years, learning media types, and educational outcomes. The analysis revealed that quantitative methodologies dominated the field (53.3%), followed by research and development approaches (26.7%) and qualitative methods (20.0%). Research activity peaked in 2024 (33%), indicating growing scholarly interest in gamification applications. All reviewed studies focused exclusively on gamification-based learning media implementation. Educational outcomes were predominantly positive, with 86.7% of studies reporting effective results in improving student learning achievements, motivation, and engagement, while 13.3% showed no significant effects. The findings validate theoretical frameworks supporting gamification's effectiveness in mathematics education while revealing implementation challenges. The high success rate supports the inherent compatibility between game-based approaches and mathematical learning processes. However, variability in outcomes emphasizes the importance of proper design alignment with learning objectives and consideration of individual student characteristics for successful implementation.